Elsimil Application to Increase Knowledge and Attitudes of Young Women to Prevent Stunting - khaerudin, didit; Utami, Karina; Lisnawati, Lisnawati (Media Informasi, 2025)
Based on the results of the Indonesian Nutrition Status Survey, the incidence of stunting in 2021 was 24.4%, and it decreased to 21% in 2022. The government continues to strive to reduce the stunting rate with a target of 14% by 2024. In 2022, the National Population and Family Agency (BKKBN) innovated through the Elsimil application to reduce the stunting rate. This study is relevant to the government's efforts to reduce the incidence of stunting. The primary objective of this study is to assess the application of Elsimil in women as prospective brides and mothers to prevent stunting. This research aims to analyze the application of Elsimil in increasing the knowledge and attitudes of teenagers regarding the prevention of stunting in Cirebon City. This is a quantitative research study, a type of quasi-experimental research with a one-group pretest-posttest design. The population is late adolescents (15-19 years old). The sample consisted of 30 young women aged 15-19 years, selected using purposive sampling. The research instrument uses a questionnaire. Univariate analysis uses frequency distribution. Bivariate analysis of the Marginal Homogeneity test for the knowledge variable yields a p-value of 0.00. The McNemar test for the attitude variable yields a p-value of 0.00. There are significant differences in knowledge and attitudes between those who used the Elsimil application before counseling and those who used it after counseling. The Elsimil application can serve as an alternative educational medium for teenagers to help prevent stunting.